Total Hip Arthroplasty with Acetabular Bone Graft Reconstruction in Neglected Fractures of the Acetabulum: A preliminary report of sixteen cases - Bassiony, Ayman Abdelaziz; Asal, Mohamed Kamal (International Journal of Orthopedics and Rehabilitation, 2016)
Background: Neglected acetabular fractures is a challenging to treat. Total hip arthroplasty with bone-graft reconstruction is among the most popular methods of providing bony support in cases of acetabular bony deficiencies during total hip arthroplasty. Controversy still exists on the best method for bony reconstruction. Patients and Methods: Sixteen patients having neglected acetabular fracture or fracture dislocation were operated for total hip arthroplasty using autograft from the femoral head. The average age of the patients was 50 years (range 36-58 years). There were 12 males and 4 females. Average time of follow up was 3 years. Results: There was graft resorption in two cases with subsequent revision. Average Harris hip score pre-operatively was 46, which improved to an average of 84 post-operatively. Conclusion: Our study has shown that total hip replacement with bone grafting in form of auto graft of the femoral head provide good results in reconstruction of acetabular bony deficiencies due to neglected acetabular fracture.